2015
DOI: 10.1155/2015/940278
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Mexican Children with Acute Myeloid Leukaemia Who Received Early Intensification Chemotherapy and an Autologous Transplant

Abstract: Background. In Mexico and other developing countries, few reports of the survival of children with acute leukaemia exist. Objective. We aimed at comparing the disease-free survival of children with acute myeloid leukaemia who, in addition to being treated with the Latin American protocol of chemotherapy and an autologous transplant, either underwent early intensified chemotherapy or did not undergo such treatment. Procedure. This was a cohort study with a historical control group, forty patients, less than 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…In this study, we investigated the regulating effect of miR-29 on K562 cells and its possible mechanism. The results showed that miR-29 overexpression inhibits human leukemia K562 cells growth and proliferation, and promotes K562 cells apoptosis, which is consistent with previous results [ 5 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, we investigated the regulating effect of miR-29 on K562 cells and its possible mechanism. The results showed that miR-29 overexpression inhibits human leukemia K562 cells growth and proliferation, and promotes K562 cells apoptosis, which is consistent with previous results [ 5 ].…”
Section: Discussionsupporting
confidence: 92%
“…At present, miRNAs with clearly defined functions includes miR-29, miR-150, miR-150, miR-181a, miR-23a, miR-148/152, miR-221/222, miR-483-3p, miR-30e, miR-397, and miR-126 [ 4 ]. Our study speculated that miR-29 may play a role through regulating transcription factors, while the other miRNAs’ regulating effect is unclear [ 3 5 ]. The miR-29 family comprises 3 isoforms arranged in 2 clusters: miR-29b-1/miR-29a in chromosome 7q32 and mir-29b-2/miR-29c in chromosome 1q23.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For consolidation courses, the most commonly used chemotherapeutic agent was cytarabine, either administered alone or in combination with an anthracycline or etoposide. During study periods from nearly twenty years ago, consolidation courses also frequently consisted of the combination of a corticosteroid (either prednisone or dexamethasone) with 6-thioguanine (6-TG) or 6-mercaptopurine (6-MP), vincristine, an anthracycline, and cytarabine, with or without cyclophosphamide [20,23,27,28,38,40,42,44]. Intensification of induction and consolidation courses consisted mainly of intermediate-or high-dose cytarabine, with or without the addition of an anthracycline or etoposide.…”
Section: Treatment Protocols and Chemotherapeutic Agentsmentioning
confidence: 99%
“…Despite the notable progression in the disease management (9, 10), the emergence of mixed-lineage leukemias, chemoresistance, and minimal residual disease decreases the probabilities for therapy success and determines relapse in more than 20% of the treated patients. As observed for the normal hematopoietic progenitors, neither premalignant cells nor leukemic blasts work as independent and autonomous entities, but they are rather surrounded in all dimensions by bone marrow (BM) niche components that provide regulatory cues essential for their cell fate decisions such as proliferation and survival (1114).…”
Section: Introductionmentioning
confidence: 99%